Pengaruh Advertising Appeal, Word Of Mouth Dan Brand Image Terhadap Keputusan Pembelian Iphone (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Susilo, Agung; Priyono, Achmad Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the advertising apeeal, word of mouth and brand image on iPhone purchasing decisions for FEB students at the Islamic University of Malang. Using multiple linear regression methods, this research focuses on explanatory research with a quantitative approach. The research sample of 75 consumers was taken using the Malhotra formula. Data analysis was carried out with the help of SPSS version 25 software, including validity test, reliability test, normality test, classical assumption test, hypothesis test, and R2 coefficient of determination test. The results showed that advertising appeal, word of mouth, and brand image simultaneously influenced consumer purchasing decisions for iPhone products for FEB students at the Islamic University of Malang. Specifically, advertising appeal and word of mouth have a partially positive impact on purchasing decisions, while brand image partially has no significant effect on consumer purchasing decisions. Keywords: Advertising Appeal, Word Of Mouth, Brand Image, Purchasing Decisions